Lithuanian Language – Native and Foreign – at School. Road to Equability - Vilkienė, Loreta (Kalbotyra, 2006)
Efforts are focused on the equalisation of the final examinations in Lithuanian at Lithuanian schools and at those of ethic minorities. The issue is whether a common examination can be equal. Can native and non-native speakers be treated as equal participants of communication in a purposive speech? There is no significant research done in this field in Lithuania. Hence, the search for answers to these issues is conducted in the works of foreign scientists. Another issue in this discussion is whether the present diverse teaching curricula of Lithuanian as a native and non-native language can lead to the conclusion that school graduates from Lithuanian schools and from those of ethnic minorities receive equal education so that they could compete during the same examination. In order to find the answers, ‘The General Curricula and the Standards of General Education at Lithuanian School of General Education. Grades XI–XII’ (2002) is analysed. The article draws the following conclusions: 1. Native and non-native speakers can theoretically become equal participants – competent speakers – in communication but only on certain conditions one of which is purposeful teaching. 2. In order to evaluate graduates’ competence in a single test, one should establish equal standards. 3. In search for an equal standard, the curricula should be made closer as the current diverse teaching curricula of Lithuanian do not point to the conclusion that school graduates receive equal education. Therefore, ‘The General Curricula and the Standards of General Education at Lithuanian School of General Education. Grades XI–XII’ does not automatically allow to equalise the final examinations in Lithuanian at present as it is doubtful whether students are well prepared to compete as equal participants of communication in Lithuanian.